Design and Fabrication of Safety Distancing Sensor for Bicycle - NurFara’ainDahlan, NurwafaAfiqah Mohamed Ali, Rafiza Abdul Razak, Chee Ken Nee, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Bicycle safety distancing sensor have attracted considerable attention to the fabrication of safety device integrated with the technology. Arduino UNO as programmable microcontroller was used along with ultrasonic sensor and LED strip to produce a functioning and smart alarming device to help the cyclist stay alert during cycling especially at night. The use of safety harness such as fluorescent jacket and lamp torch on the cyclist bicycle itself may not be sufficient for their safety. Hence, the usage of bicycle safety distancing sensor or name as (UNO-Bike) can help the cyclist to ride with more confident. The sensor will detect any upcoming vehicles from behind of the cyclist and warned them by blinking and changing of colour of the LED strip from green to red. There is no invention of safety distancing sensor for bicycle currently, hence our product has an advantage on the novelty, and it is a cost-efficient product as it uses Arduino which is very user-friendly on the cost and the mechanisms.